Early Self-Regulation, Early Self-Regulatory Change, and Their Longitudinal Relations to Adolescents' Academic, Health, and Mental Well-Being Outcomes - Howard, Steven J.; Williams, Kate E (My University, 2018)
To evaluate the extent to which early self-regulation and early changes in self-regulation are associated with adolescents' academic, health, and mental well-being outcomes. Data were collected from 1 of the cohorts in a large dual-cohort cross-sequential study of Australian children. This cohort consisted of a nationally representative data set of 4983 Australian children assessed at 4 to 5 years of age, who were followed longitudinally to 14 to 15 years of age. Using regression within a path analysis framework, we first sought to investigate associations of early self-regulation (at 4-5 years and 6-7 years of age) with a broad range of academic, health, and mental well-being outcomes in adolescence (at 14-15 years). We next investigated the extent to which an early change in self-regulation (from 4 to 7 years of age) predicted these adolescents' outcomes. Early self-regulation predicted the full range of adolescents' outcomes considered such that a 1-SD increase in self-regulation problems was associated with a 1.5- to 2.5-times greater risk of more-negative outcomes. An early positive change in self-regulation was associated with a reduced risk of these negative outcomes for 11 of the 13 outcomes considered. These results suggest the potential of early self-regulation interventions, in particular, in influencing long-term academic, health, and well-being trajectories.
Journal of Developmental and Behavioral Pediatrics
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing; Learning, education and training